Hodgkin's disease presenting as discharging neck sinuses and a mediastinal mass. (29th July 2011) - Zolotar, Meira; Olaleye, Oladejo; Sherif, Ali; Howe, Rachael; Mathews, John
Abstract : A 23-year-old Asian lady presented with a hard indurated midline neck swelling of 2 months duration without any upper aerodigestive tract or systemic symptoms of note. Her inflammatory markers were elevated and she was commenced on antibiotics. Ultrasound scan and fine needle aspiration cytology (FNAC) were inconclusive. A CT scan showed an ill-defined soft tissue mass anterior to and not well demarcated from the thyroid, and contiguous with a superior and anterior mediastinal mass. Incisional biopsy revealed necrosis and pockets of purulent material. Microbiology suggested a chronic pyogenic abscess negative for acid fast bacilli. She was treated with antituberculous therapy without resolution. She developed a discharging lateral neck mass with progressive increase of the mediastinal mass. She subsequently required a neck exploration and mediastinoscopy. Repeat mediastinal biopsies confirmed the diagnosis of Hodgkin's disease and no organisms on culture. She was commenced on chemotherapeutic treatment with a satisfactory outcome.